Matrix stiffness primes lymphatic tube formation directed by vascular endothelial growth factor‐C. Issue 5 (27th March 2021) - Alderfer, Laura; Russo, Elizabeth; Archilla, Adriana; Coe, Brian; Hanjaya‐Putra, Donny
Abstract: Dysfunction of the lymphatic system is associated with a wide range of disease phenotypes. The restoration of dysfunctional lymphatic vessels has been hypothesized as an innovative method to rescue healthy phenotypes in diseased states including neurological conditions, metabolic syndromes, and cardiovascular disease. Compared to the vascular system, little is known about the molecular regulation that controls lymphatic tube morphogenesis. Using synthetic hyaluronic acid (HA) hydrogels as a chemically and mechanically tunable system to preserve lymphatic endothelial cell (LECs) phenotypes, we demonstrate that low matrix elasticity primes lymphatic cord‐like structure (CLS) formation directed by a high concentration of vascular endothelial growth factor‐C (VEGF‐C). Decreasing the substrate stiffness results in the upregulation of key lymphatic markers, including PROX‐1, lymphatic vessel endothelial hyaluronan receptor 1 (LYVE‐1), and VEGFR‐3. Consequently, higher levels of VEGFR‐3 enable stimulation of LECs with VEGF‐C which is required to both activate matrix metalloproteinases (MMPs) and facilitate LEC migration. Both of these steps are critical in establishing CLS formation in vitro. With decreases in substrate elasticity, we observe increased MMP expression and increased cellular elongation, as well as formation of intracellular vacuoles, which can further merge into coalescent vacuoles. RNAi studies demonstrate that MMP‐14 is required to enable CLS formation and that LECs sense matrix stiffness through YAP/TAZ mechanosensors leading to the activation of their downstream target genes. Collectively, we show that by tuning both the matrix stiffness and VEGF‐C concentration, the signaling pathways of CLS formation can be regulated in a synthetic matrix, resulting in lymphatic networks which will be useful for the study of lymphatic biology and future approaches in tissue regeneration.